Can self-assertion be targeted in doping prevention. Actions among adolescent athletes? A randomized controlled trial - Laure, P.; Favre, A.; Binisinger, C.; Mangin, G. (Serbian Journal of Sports Sciences, 2009)
Objective: to study the feasibility of the development of self-assertion among adolescent athletes in doping prevention campaigns. Design: randomized controlled trial. Methods: Participants: pupils aged 10-16 of school sporting clubs randomized in an experimental (EXP) or acontrol (CON) group. Interventions: EXP: 2 x 2 hours, at three month intervals (M0 and M+3): law recall, information on self-medication, series of activities that build self-assertion; CON: none. Evaluation: self-questionnaire at M0 and M+3, containing a Rathus Assertiveness Schedule. Main results: At M0, mean Rathus' scores were identical in EXP and CON groups (4.9 - 4.3). They both rose three months later, but the increase was more significant in EXP (6.2) than in CON (4.5) group (p<0.001), especially among pupils aged 10-11 years, in sporting clubs made up of fewer than 20 pupils, and among pupils who practiced more than 10 hours of sports per week. Conclusions: Selfassertion can be improved among early adolescent athletes with a 2 x 2 hours' intervention. This constitutes an interesting "brief intervention" for clubs bound by time constraints.